Cyberchondria: A new clinical entity in the context of the COVID-19 pandemic - Ovalle-Quiñones, Milluska (2021)
Introduction. We live in a globalized world that is kept connected through the internet. Determining the veracity of the information we receive is difficult, even more so in that related to health. The internet is one of the most popular sources for the search for health-related information and this behavior increases in the context of epidemiological outbreaks. In the context of the current pandemic, an increase in anxiety about health issues has been found, the main concern being being infected by SARS-CoV-2. Search strategy: A search was carried out in the PubMed database of all articles published up to June 30, 2020. The search for terms included the keywords suggested by the controlled vocabulary Medical Subjects Headings (MeSH) and connectors. Cyberchondria, COVID-19 and Mental Health: The role of the media is crucial, because it could induce anxiety in the population. Cyberchondria involves experiencing anxiety after searching for medical information and addressing health problems online. It originates as a behavior that seeks the feeling of security, however, it is repetitive and excessive, which leads to worse worries. One of the risks is that patients develop distrust of the doctor and a greater likelihood of self-medication. The prevalence of this entity, in our country and in many others, is unknown. In the context of this pandemic, it is important that research focuses on finding an effective drug or vaccine soon; however, we must not ignore the mental health of the population, which has been impacted by all the social changes in our lives. Conclusions: Cyberchondria is a new clinical entity, which leads to the excessive and repetitive search for information on health issues on the internet; increasing anxiety in people. In the context of the current pandemic, it is necessary to evaluate this aspect.